Selenium content of native bluestem pastures - L.H. Harbers; D.A. Sapienza; L. Schwanke; S.M. Kazemi; E.F. Smith (Kansas Agricultural Experiment Station Research Reports, 1981)
We used steers with esophageal cannulas to measure selenium in burned and unburned bluestem pastures between May and September. Individual variation among steers sampled varied as much as two fold in selenium content. All values were considered adequate for cattle.
Keywords: Cattlemen' s Day; 1981; Report of progress (Kansas State University. Agricultural Experiment Station); 394; Beef; Selenium content; Bluestem pastures